POLA BUKU AJAR PENDIDIKAN LINGKUNGAN HIDUP (PLH) SEBAGAI MATA PELAJARAN MUATAN LOKAL SEKOLAH DASAR UNTUK MENDUKUNG IMPLEMENTASI PENDEKATAN SAINTIFIK - Susriyati Mahanal; Sugeng Utaya (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Environmental education (PLH) is important to give in elementary school (SD) early. PLH not only give knowledge and understanding, but also shaping behavior and forming positive attitudes of students on the environment. PLH’s textbook being an important tools to support the implementation of PLH’s learning. However, in some districts/ cities that have been declared as local content PLH (local content) in elementary education, haven’t PLH’s textbooks sufficiently and in accordance with the needs of the field until now. Therefore PLH’s textbook procurement must be realized. In accordance with the 2013 curriculum elementary school PLH’s textbooks is being developed to support scientific approach based learning that includes observing, questioning, associating, experimenting, and networking. The teaching materials is packed with features, “Let’s understand”. The learning activities is packed with features, “Let’s work together”, “Let’s try”, and “Let’s tell. The concept map is packed with features, “Let’s study”. The summary is packed with features, “Let’s summarize. The reflection is packed with features, “Let’s reflect”. This structures not only empower the thinking skill but also encourages the achievement of positive attitudes and behaviors towards the environment.     Keywords: Development, Text book, Environmental education